Peter Berger and the study of religion - Martin, David; Woodhead, Linda; Heelas, Paul; Berger, Peter L. (Routledge, 2001)
Peter Berger is the most influential contemporary sociologist of religion. This collection of essays is the first in-depth study of his contribution to the field